The Relationship between Environmental Sanitation and Personal Hygiene Factors with Stunting Incidents in Toddlers in the Work Area of the Rejosari Pekanbaru Health Center in 2022: Hubungan Faktor Sanitasi Lingkungan Dan Personal Hygiene Dengan Kejadian Stunting Pada Balita Di Wilayah Kerja Puskesmas Rejosari Pekanbaru Tahun 2022 - Wiwiek Rismawatiningsih; Christine Vita G.P; Sherly Vermita; Sri Desfita; M. Kamali Zaman (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Stunting is associated with impaired brain development, which in the short term affects cognitive ability, and in the long term reduces the capacity for better education and loss of opportunity for better income employment opportunities. The stunting prevalence rate in Pekanbaru City in 2019 was 9%. The number of stunting rates in 2020 reached 668 people with the highest number being in Rejosari Village with 230 cases with a prevalence of 9.793%. The purpose of the study was to determine the relationship between environmental sanitation and personal hygiene factors with the incidence of stunting in toddlers in the Rejosari Pekanbaru Health Centre working area. This study was quantitative analytical observational using case control research design conducted in the working area of Puskesmas Rejosari Pekanbaru in June - July 2022. The case population is toddlers who experience stunting who visit the Rejosari Pekanbaru Health Centre. The control population is toddlers who are not stunted in toddlers in the working area of Puskesmas Rejosari Pekanbaru. The case sample was 87 toddlers who were stunted with a ratio of 1: 1 then the control group sample was 87 people so that the total sample was 174 respondents. The sampling technique was consecutive sampling. Data collection using a questionnaire. Data analysis using univariate and bivariate analysis. The results of the study can be concluded that there is a relationship between hand washing with soap, personal hygiene of toddlers with the incidence of soap stunting (p value = < 0.05), There is no relationship between clean water quality, condition of household sewerage with the incidence of stunting (p value = > 0.05). It is hoped that the health centre will be more intensive in making visits to the toddler's house to provide advice on personal hygiene.